Losing Sleep at the Market: The Daylight Saving Anomaly: Reply - Kamstra, Mark J; Kramer, Lisa A; Levi, Maurice D (American Economic Review, 2002)
Losing Sleep at the Market: The Daylight Saving Anomaly: Reply by Mark J. Kamstra, Lisa A. Kramer and Maurice D. Levi. Published in volume 92, issue 4, pages 1257-1263 of American Economic Review, September 2002